THE MAIN CHARACTER’S STRUGGLES TO FIGHT AGAINST PATRIARCHAL IDEOLOGY IN GRETA GERWIG’S BARBIE (2023) - Kanisdi Nur Maydita; Agnes Setyowati; Erol Kurniawan (PT. Media Akademik Publisher, 2026)
The film Barbie (2023), directed by Greta Gerwig, represents the discourse of patriarchy that frequently emerges within social environments and often disadvantages women. This study aims to analyze how patriarchal discourse is constructed and represented through the character of Barbie, as well as to examine Barbie’s forms of resistance against such discourse. The research employs a feminist approach and cultural studies framework, utilizing Stuart Hall’s concept of representation to explore the power relations embedded within the patriarchal narrative presented in the film. This is a qualitative descriptive study, and the data were analyzed using Gillian Rose’s visual methodology. The findings reveal that the character of Barbie embodies a woman constrained by patriarchal structures but gradually develops resistance through collective awareness alongside other female characters. This resistance illustrates a rejection of male dominance within the social and cultural structure of Barbieland. The film not only critiques patriarchal systems that are detrimental to women but also offers a portrayal of the importance of solidarity and collective consciousness in challenging structures that limit women’s freedom and identity.